2011
DOI: 10.1007/s10620-011-1774-z
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of Different DNA Repair Genes Demonstrates Distinct Prognostic Value for Esophageal Cancer

Abstract: Promoter CpG island methylation may be a frequent event in ESCC carcinogenesis. Detection of the methylated sequences of hMLH1, hMSH2, and MGMT appears to be promising as a predictive factor in primary ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
(62 reference statements)
0
28
1
Order By: Relevance
“…The current results demonstrated that no correlation was found between MGMT promoter methylation and gender, cigarette smoking, or drinking behavior, which were consistent with the results of an individual study. Baumann et al [36] reported the correlation between MGMT promoter methylation and tumor differentiation among 132 patients, but other 2 studies involving 335 patients showed no correlation between MGMT promoter methylation and tumor differentiation [27,29]. The current results demonstrated that MGMT promoter methylation was not linked to tumor differentiation.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The current results demonstrated that no correlation was found between MGMT promoter methylation and gender, cigarette smoking, or drinking behavior, which were consistent with the results of an individual study. Baumann et al [36] reported the correlation between MGMT promoter methylation and tumor differentiation among 132 patients, but other 2 studies involving 335 patients showed no correlation between MGMT promoter methylation and tumor differentiation [27,29]. The current results demonstrated that MGMT promoter methylation was not linked to tumor differentiation.…”
Section: Discussioncontrasting
confidence: 46%
“…Based on the selection criteria for the eligible studies, eventually 17 articles were identified in this meta-analysis [21,22,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] these studies included a total of 1,368 patients with esophageal carcinoma and 1,489 nonmalignant controls. Sixteen studies evaluated the association between MGMT promoter methylation and esophageal carcinoma risk in cancer vs. nonmalignant controls [21,22,[28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Eight studies with 928 esophageal carcinoma patients analyzed the correlation between MGMT promoter methylation and the clinical features [21, 27-30, 32, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no loss of DNA methylation in oral cells was detected. Other studies have found changes in the DNA methylation of MLH1 gene compared with healthy individuals with individuals with cancer, and hypermethylation was detected in colorectal cancer (Kane et al 1997), gastric cancer (Alves et al 2011), esophagic cancer (Ling et al 2011) and lung cancer (Gomes et al 2014). These studies also found association between hypermethylation and gene repression.…”
Section: Resultsmentioning
confidence: 82%
“…MLH1 encodes a protein that has been implicated in the maintenance of genome stability during DNA replication (21)(22)(23). A previous study indicated that MLH1 promoter hypermethylation was able to inactivate gene transcription, inducing defects in the function of the DNA repair system (24). Therefore, MLH1 contributes to the subsequent development of tumors including ESCC (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that MLH1 promoter hypermethylation was able to inactivate gene transcription, inducing defects in the function of the DNA repair system (24). Therefore, MLH1 contributes to the subsequent development of tumors including ESCC (24,25). MLH1 promoter methylation is significantly higher in EC tissues, as compared with paired adjacent tissues (15); however, the association between MLH1 promoter methylation and the prognosis of EC has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%